Venous thrombosis associated with pancreatic cancer - Vlad Buică; Camelia Cristina Diaconu; Octavian Andronic (Journal of Mind and Medical Sciences)
Introduction. Cancer-associated thrombosis is a significant prognostic marker in pancreatic neoplasia, with a venous thromboembolism incidence of 17-34%. This study focuses on cancer-associated thrombosis risk factors, screening scores, and treatment options. Materials and Methods. Comprehensive database searches were conducted across Web of Science, PubMed, Reaxys, ScienceDirect, and Scopus. Results. Of the 37 articles reviewed, findings include splanchnic vein thrombosis correlating with pancreatic complications and survival rates. Gender differences in cancer-associated thrombosis risk were inconclusive, while African Americans showed a higher incidence of pulmonary embolism. Various cancer-associated thrombosis staging scores were evaluated, with ONKOTEV score outperforming Khorana. Direct oral anticoagulants were suggested as viable alternatives to low molecular weight heparins. Non-anticoagulant sulfated low molecular weight heparin emerged as a future option, offering reduced bleeding risks with similar efficacy. Conclusions. Managing cancer-associated thrombosis in pancreatic cancer is challenging, highlighting the need for improved understanding, better screening methods, and more effective treatments.